WAHYU DAN TRADISI SEBAGAI SUNATULLAH: Analisis Pemikiran Nurcholish Madjid tentang Politik Islam Di Indonesia - Julianus Eduardus (Integritas Terbuka: Peace and Interfaith Studies, 2026)
This study aims to analyze the relationship between revelation, tradition, and reason in the thought of Nurcholish Madjid and to explain its relevance to the development of Islamic politics in contemporary Indonesia. This study is important because debates concerning the relationship between Islam, modernity, and politics continue amid the growing tendency toward the formalization of religion in the public sphere. The study employs a qualitative approach and collects data through library research. The findings show that Nurcholish Madjid’s thought centers on tawhid as an epistemological principle that connects revelation, tradition, and reason through the concept of sunnatullah. He understands tradition as a source of values that must be dynamically reinterpreted to respond to social change, while he views modernization as an internal process that remains consistent with Islamic values. This framework generates a substantive vision of Islamic politics that prioritizes justice, democracy, pluralism, and public welfare over religious symbolism. The relevance of this perspective appears in the development of Indonesian Islamic politics, which demonstrates a gradual shift from formalism toward substantivism. This study contributes to the literature by demonstrating that the concept of sunnatullah functions as an epistemological bridge between revelation, tradition, and reason in the construction of substantive Islamic politics. These findings expand interpretations of Islamic neo-modernism within the context of contemporary Indonesia.